Respons Bibit Bud Chips Batang Atas, Tengah, dan Bawah Tebu (Saccharum officinarum L.) terhadap Aplikasi Dosis Mulsa Bagasse - Irianti, Silviana; Indrawati, Wiwik; Kususmastuti, Any (Jurnal Agro Industri Perkebunan, 2017)
There are many benefits of sugarcane (Saccharum officinarum L.) as a sugar source to fulfil human staples food. The use of sugarcane bud chips is one of cultivation technology in order to achieve national sugar self-sufficiency program. Bagasse mulch kept soil moisture and increased organic matter in the soil thathas positive impact on sugarcne growth. The experiment was conducted in Teaching Farm of the State Polytechnic of Lampung, from November 2015 until April 2016. The experiment used Randomized Block Design (RBD) in factorial pattern, consisting of two factors. The first factor is the treatment of bud chips position consisting of 3 levels i.e. top bud chip, middle bud chip, and bottom bud chips. The second factor is the bagasse mulch treatment consisting of 4 levels i.e. control, 3 ton.ha-1, 6 ton.ha-1, and 9 ton.ha-1. The objectives of the study were to obtain optimal growth among bud chips, optimal bagasse mulch, and to know the interaction between the bud chips position and the bagasse treatments. The results showed that the top bud chips were better than  middle bud chips and bottom bud chips. The optimal rate of bagasse mulch was 3 ton.ha-1. There was an interaction between the treatment of sugarcane bud chips and mulch bagasse on leaf length and soil moisture growth.   Keywords: bagasse mulch, bud chips, sugarcane seedlingsPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/648